A new species of planthopper in the genus Eumyndus (Hemiptera: Cixiidae) from palms in eastern Madagascar and molecular evidence for the synonymy of Eumyndus kraussi and Eumyndus metcalfi - Bahder, Brian W.; Randretsiferana, Safidinirina Armande; Randretsiferana, Andrianatenaina; Stroiński, Adam; Łukasik, Piotr; Bartlett, Charles R.; Pilet, Fabian; Hasinjaka, Rasolondalao Harin’hala (Zootaxa, 2024)
A new species of Eumyndus Synave, 1956, a genus endemic to Madagascar, is here described as Eumyndus jeanjacquei sp. nov. The new species was collected from the palm Vonitra fibrosa (C.H.Wright) Becc., 1911. Molecular data are provided for the new species from the barcoding region (5’ half) of the cytochrome c oxidase subunit I (COI) gene, 18S rRNA gene and D9-D10 expansion region of the 28S rRNA gene and support placement of the new species in Eumyndus. A new synonymy is proposed based on examination of type material: E. metcalfi Synave, 1956 equals E. kraussi Synave, 1956, new synonym.